2011
DOI: 10.5194/amt-4-1689-2011
|View full text |Cite
|
Sign up to set email alerts
|

First national intercomparison of solar ultraviolet radiometers in Italy

Abstract: It involved 8 institutions, 10 broadband radiometers, 2 filter radiometers and 2 spectroradiometers. Synchronized measurements of downward global solar UV irradiance at the ground were collected and the raw series were then individually processed by the respective operators on the base of their own procedures and calibration data. A radiative transfer model was successfully applied as an interpretative tool. The input parameters and output results are described in detail. The comparison was performed in terms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 32 publications
5
38
0
Order By: Relevance
“…The Aosta monitoring site is a semi-rural site at the North-Western Alps, inside the Aosta Valley. Tall mountains at the north and the south of the Aosta station block the horizon up to an elevation of 20 • [106]. Ancillary ground based and satellite measurements of other parameters were also used and discussed further below.…”
Section: Uv In Rome and Aostamentioning
confidence: 99%
See 1 more Smart Citation
“…The Aosta monitoring site is a semi-rural site at the North-Western Alps, inside the Aosta Valley. Tall mountains at the north and the south of the Aosta station block the horizon up to an elevation of 20 • [106]. Ancillary ground based and satellite measurements of other parameters were also used and discussed further below.…”
Section: Uv In Rome and Aostamentioning
confidence: 99%
“…The integral of erythemal irradiance over a certain time period is usually referred as the erythemal dose. Highly accurate spectral measurements can be also used for the calibration and/or the validation of broad-band and narrow-band instruments [90,97,106] used to directly measure UV index.…”
Section: Introductionmentioning
confidence: 99%
“…In addition several recent studies suggested the possible protective role of vitamin D in some neoplasias of internal organs [1]. The latitude extension and the variety of environmental conditions of the Mediterranean as well as of the Alpine regions make solar UV measurements an important issue in Italy [2] where, however, a climatological characterization of biologically effective UV radiation is still missing. Given the dual nature (beneficial and harmful) of the effects of UV radiation on human health, we derived a climatological characterization of erythemal and vitamin D dose rates at two Italian sites with different environmental conditions: Rome (urban site: 41.9°N,12.5°E, 70 m a.s.l) and Aosta (semirural site: 45.8°N, 7.4°E, 569 m a.s.l) in relation to total ozone (TO), solar zenith angle (SZA) and aerosol optical index (AI).…”
Section: Introductionmentioning
confidence: 99%
“…The pre-vitamin D 3 [3] and the erythemal [4] action spectra were normalized at 298 nm. UV spectra of both sites were corrected for angular response and temperature [2,5]. To check for any spectral wavelength shift and spectral anomalies the SHICrivm software (version 3_075) was applied to the data [7].…”
Section: The Measurementsmentioning
confidence: 99%
“…In addition, UV doses were also recorded by a broad-band radiometer (same model as in Plateau Rosà) operational since 2004 at the headquarter of ARPA Valle d'Aosta (Aosta Valley Regional Environmental Protection Agency) at Saint Christophe, Aosta. Both radiometers belong to ARPA Valle d'Aosta and provide the erythemal dose rate between 280 and 400 nm with a sampling time of 10 s. The instruments are characterize every year at the PMOD/WRC (Physikalisch-Meteorologisches Observatorium Davos, World Radiation Center, see http://www.pmodwrc.ch/euvc/ euvc.html), and absolutely calibrated at Aosta with reference to a double monochromator spectroradiometer traceable to the QASUME World standard (Gröbner et al, 2005;Diémoz et al, 2011).…”
Section: Instrumentationmentioning
confidence: 99%